2016
DOI: 10.1111/1365-2664.12607
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate and habitat heterogeneity as the major drivers of beetle diversity in dead wood

Abstract: 1. Resource availability and habitat heterogeneity are principle drivers of biodiversity, but their individual roles often remain unclear since both factors are usually correlated. The biodiversity of species dependent on dead wood could be driven by either resource availability represented by dead-wood amount or habitat heterogeneity characterized by dead-wood diversity or both. Understanding their roles is crucial for improving evidence-based conservation strategies for saproxylic species in managed forests.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
156
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 225 publications
(181 citation statements)
references
References 54 publications
9
156
0
2
Order By: Relevance
“…Compared to previous results (Paillet et al., ), the negative result for saproxylic beetles is more surprising, but may be due to the fact that most of the reserves we studied are relatively young and display relatively small amounts of favourable habitats and features compared to other European references (Bouget, Parmain, et al., ; Paillet, Pernot, et al., ). As a consequence, stands may still be in an accumulation phase where light conditions are probably not diverse enough to favour both forest specialists and light‐demanding species at a small scale (see e.g., Bouget, Larrieu, et al., ; Seibold et al., for saproxylic beetles) and the potential effect of microhabitats or large structural elements may be masked by such unfavourable light conditions (Miklín et al., ). It is thus important to take the temporal dimension of this result into account and we may expect biodiversity to increase when the reserves would be mature enough to show spatial horizontal heterogeneity at the stand scale (Paillet, Pernot, et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to previous results (Paillet et al., ), the negative result for saproxylic beetles is more surprising, but may be due to the fact that most of the reserves we studied are relatively young and display relatively small amounts of favourable habitats and features compared to other European references (Bouget, Parmain, et al., ; Paillet, Pernot, et al., ). As a consequence, stands may still be in an accumulation phase where light conditions are probably not diverse enough to favour both forest specialists and light‐demanding species at a small scale (see e.g., Bouget, Larrieu, et al., ; Seibold et al., for saproxylic beetles) and the potential effect of microhabitats or large structural elements may be masked by such unfavourable light conditions (Miklín et al., ). It is thus important to take the temporal dimension of this result into account and we may expect biodiversity to increase when the reserves would be mature enough to show spatial horizontal heterogeneity at the stand scale (Paillet, Pernot, et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In a second step, we used a similar model including the number of individuals (log) as explanatory variable for the species richness similarly to Seibold et al . (). By this, we tested whether effects on species richness were caused by a change in the abundance of saproxylic beetles.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the importance and diversity of wood‐inhabiting fungi, our understanding of the factors driving the spatial and temporal patterns of their diversity is limited. It has been suggested that characteristics of the colonized dead‐wood object (host) and the environment surrounding an object are important drivers of the diversity of wood‐inhabiting fungi (Heilmann‐Clausen et al., ; Seibold, Bässler, Brandl, et al., ; Seibold et al., and therein). However, how the host and the environment individually affect fungal diversity on dead‐wood objects is unknown (Bradford et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…This correlation is not surprising as forest gap dynamics caused by anthropogenic disturbances, for example, logging, or natural disturbances, for example, windthrows, insects, fire or snow, is an important driver influencing the diversity of forest species across numerous taxa at the landscape scale (Swanson et al., ). Variation in canopy openness is physically correlated to changes in moisture and temperature regimes and to fluctuations of these variables also within a dead‐wood object (Scharenbroch & Bockheim, ; Seibold, Bässler, Brandl, et al., ). Variation in microclimate within dead wood can therefore have pronounced effects on the fungal community (Boddy & Heilmann‐Clausen, ; Pouska, Macek, Zíbarová, & Ostrow, ).…”
Section: Introductionmentioning
confidence: 99%